RICKETIS IN CHILDREN: CLINICAL PICTURE, DIAGNOSIS AND TREATMENT - Ibatova Sh.M; Rakhmonov Yu. A; Sanakulov A.B. (Western European Studies, 2024)
Rickets is a disease that has been known to mankind for many centuries. It is known that vitamin D plays a significant role in the regulation of calcium and phosphorus homeostasis and, consequently, in the development of rickets. The main etiological factor of rickets is considered to be insufficient exposure of children to ultraviolet sunlight. This article presents the clinical picture, diagnostics and treatment of rickets.
Keywords: rickets; children; calcium